Effect of ferrocement jacketing on the flexural behaviour of beams with corroded reinforcements. (15th September 2016) - Jayasree, S.; Ganesan, N.; Abraham, Ruby
Highlights: Influence of cover thickness and strength of concrete on accelerated corrosion was investigated. Effect of corrosion on the flexural behaviour of RC beams was studied. Flexural behaviour of corroded RC beams after retrofitting with ferrocement jacketing was evaluated. Abstract: Corrosion of reinforcement is one of the main causes of deterioration of Reinforced Cement Concrete (RCC) structures which affects the load carrying capacity and its durability. Though it is very difficult to completely eliminate the chances of corrosion, suitable retrofitting strategies can be introduced as a measure for the retrofitting of corrosion damaged structures to gain its original strength. The present work deals with the study of degradation of the ultimate load carrying capacity of the flexural members due to corrosion. Twenty-one RCC beams were cast, out of which, three beams were kept as control specimens, and the remaining were subjected to varying levels of corrosion (5, 10 and 15%) so that six specimens are obtained for each level of corrosion. Accelerated corrosion was induced by means of impressed current method. From each level of corrosion, three beams were subjected to loading corresponding to 70% of the ultimate load given by the remaining three specimens corresponding to that level of corrosion. Subsequently these beams were retrofitted by means of a U-wrap ferrocement jacketing. All the beams were tested under two point loading and the strength and behaviour of retrofitted beams were compared with control specimens.